Disestablishing Deism: Advocating Free Exercise Challenges to State-Induced Invocations of God - Michael Blank (Washington University Journal of Law & Policy, 2009)
The popularity of Atheist literature contrasts sharply with the prevalence of god and religion in American public life. The privileged status of religion in America leads to some frustration amongst Atheists who have tried and failed to prevent the state from invoking god. This Note will suggest that Atheists should challenge state-induced invocations of god under the Free Exercise Clause. Because of the difference in doctrine, Free Exercise challenges may succeed where Establishment Clause challenges have failed. More specifically, this Note will examine four instances of so-called ceremonial deism: the Pledge of Allegiance, legislative prayer, oaths of office, and oaths of witnesses.
Keywords: Religion; Free exercise clause (Constitutional law); Atheism; Church and state; Deism; Freedom of religion